Analysis of artery injury types and clinical characteristics of patients with transcatheter angioembolization after percutaneous nephrolithotomy - Meng, Xianghu; Cong, Rong; Hua, Yibo; Wang, Zengjun; Song, Ninghong; Yang, Wei; Song, Rijin (Frontiers in Surgery, 2025)
BackgroundThere is no systematic classification of renal vascular injuries conducted for severe post-percutaneous nephrolithotomy (PCNL) bleeding.AimThe aim of the present study was to explore the various types of artery injury and clinical characteristics of patients who underwent transcatheter angioembolization (TAE) after PCNL.MethodsA retrospective analysis was performed on 52 patients who underwent renal arteriography (RA) because of severe bleeding after PCNL between April 2009 and December 2023. Among the patients, 38 underwent TAE due to positive RA results. Clinical data on the TAE patients, such as gender, age, body mass index, TAE interval, hemoglobin (Hb) decrease, operation time, stone size, the number and size of tracts, and clinical bleeding type, were summarized. The types of artery injury in TAE patients and their relationships with clinical characteristics were analyzed.ResultsRetrospective analysis revealed that, among the 38 TAE patients (32 males and 6 females), the mean TAE interval, average Hb decrease, mean tract number, and mean tract size reached 5.00 (6.25) days, 44.50 (24.50) g/L, 1 (0.25), and F20(6), respectively. Among the TAE patients, four kinds of vascular injury were observed, namely, 18 cases of pseudoaneurysm (PA), 12 cases of arteriocaliceal fistula (ACF), 7 cases of arteriovenous fistula (AVF), and 1 case of arterioperirenal fistula (APF). Analysis of the clinical characteristics of the three types of vascular injury (PA, ACF, and AVF) revealed that the number of tracts was the only factor that differed.ConclusionThe RA results indicate that the types of postoperative renal artery injury mainly include PA, ACF, AVF, and APF, and the number of tracts may be related to the type of vascular injury.